Immigrant Children's Adaptation: An Ecortitical study of the - Sami Majeed, Rafid (Al-Adab Journal, 2021)
When a person gets used to a place where he was born and grew up and adapts to people and the environment around him and becomes an integral part of them, it would be difficult if he is forced, by any means, to leave the place and abandon these people ,leaving them behind. Migration, whether voluntary or compulsory, has its negative effects. A migrant may need many years to forget the effects of the moves he did and perhaps will not forget their influence on him throughout his life, especially if he is forced to move for certain circumstances and will definitely need someone (s) to help him feel secure and safe in the new environment, and that will relieve him of his feelings of emptiness, irrelevance and isolation. It is part of human nature to live in social and communicative societies, not in isolation and detachment. Migrant children are the most affected people in these moves. Juan Felipe Herrera believes that it is the duty of the new society to which immigrants are moved to accept and help them, not to impose tough and inconsiderate laws or put other obstacles before them. These immigrants are already loaded with concerns and worries and need no more trouble to suffer. He insists that attention to these children is a human duty, which, when done, can assists them to adapt environmentally, socially and psychologically to their new societies. In The Upside Down Boy, Juanito, the immigrant child feels lost at the first days he is in the new school and that everything is upside down for him when his family moved from Mexico to San Francisco. Herrera, himself a Mexican immigrant, tells people about the situations juanito suffers and calls them to help him to set things up right once more.